HI 1634 (Pusa Ahilya), high yielding bread wheat variety tolerant to terminal heat stress conditions of Central Zone - Prasad, Sakuru Venkata Sai; Singh, Jang Bahadur; Ambati, Divya; Phuke, Rahul Madhav Rao; Prakasha, Thorehalli Linganna; Mishra, Akilesh Nandan; Sharma, Kailash Chandra; Singh, Anil Kumar; Verma, Dalip Kumar; Singh, Gyanendra Pratap; Sharma, Jai Bhagwan; Singh, Pradeep Kumar; et al. (Journal of Cereal Research, 2022)
HI 1634 (Pusa Ahilya), a high yielding bread wheat variety with an average yield of 51.6 q/ha was released by Central Sub-Committee on Crop Standards, Notification and Release of Varieties for Agricultural Crops, Government of India vide notification No. S.O. 500 E dated 29.01.2021 for commercial cultivation under late sown irrigated conditions of central wheat growing zone of India. HI 1634 performed superior when grown under various sowing conditions with seedling and adult plant resistance to all pathotypes of stem and leaf rusts which are virulent in India and postulated to have stem rust gene Sr31. HI 1634 had an excellent chapati quality and bread making quality along with good levels of essential micronutrients like iron and zinc content. HI 1634 will be a high yielding and terminal heat tolerant bread wheat variety ensuring better market price for farmers and will be a new option for the millers and baking industries.Â